Development of emotional awareness for children aged (5-6-7 ) (Journal of the College of Basic Education, 2020)
The aim of this research is to identify the emotional awareness for children aged 5-6 7- And emotional awareness for children by gender The sample consisted of 150 children, 50 children, kindergarten children, 50 children and pre-school girls, 50 children Of the first grade of primary and used the researcher's emotional awareness scale, which was prepared by the researcher After reviewing the previous studies and the theoretical background and using the statistical bag showed that the emotional awareness of children develops with age and the older the child the greater awareness of the actions.